2017
DOI: 10.1515/ppb-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Polish Version of the Short Grit Scale

Abstract: This study aimed to verify the psychometric properties of the Polish version of the Grit-S questionnaire. Grit is understood here as the perseverance and passion for long-term goals, and it encompasses two dimensions: Consistency of Interest and Perseverance of Effort. The sample comprised N = 270 participants aged 18-34 (Mage = 20.79). We performed confirmatory factor analyses to verify the dimensional structure of grit, multi-group confirmatory factor analysis to compare the structure across gender, and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 29 publications
7
21
0
5
Order By: Relevance
“…The eight-item Grit-S has become a popular tool to measure grit across nations. The Grit-S scale has been the subject of a few validation studies and has been translated into, for example, German (Schmidt et al, 2017), Spanish (Arco-Tirado et al, 2018), and Polish (Wyszyńska et al, 2017). Within applied studies, the Grit-S scale has successively produced various factor structures ranging from an overall one factor model, to a threefactor model (Datu et al, 2015;Hatchimonji, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The eight-item Grit-S has become a popular tool to measure grit across nations. The Grit-S scale has been the subject of a few validation studies and has been translated into, for example, German (Schmidt et al, 2017), Spanish (Arco-Tirado et al, 2018), and Polish (Wyszyńska et al, 2017). Within applied studies, the Grit-S scale has successively produced various factor structures ranging from an overall one factor model, to a threefactor model (Datu et al, 2015;Hatchimonji, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that item 2 contains double negative words (e.g., don't discourage) thus difficult for non-native English speakers to comprehend the meaning of the item (Lavrakas, 2008). In line with this assumption, item 2 was found acceptable in the translated versions of Grit-S (e.g., Li et al, 2018;Nishikawa et al, 2015;Schmidt et al, 2017;Wyszyńska et al, 2017). Moreover, Muenks et al (2017) found that item 2 was found acceptable for American college students but not high school students.…”
Section: Discussionmentioning
confidence: 71%
“…Li and colleagues (2018) indicated that the Chinese version of Grit-S is suitable for adolescents in China. In addition, the German version (Schmidt, Fleckenstein, Retelsdorf, Eskreis-Winkler, & Möller, 2017), Japanese version (Nishikawa, Okugami, & Amemiya, 2015), and Polish version (Wyszyńska, Ponikiewska, Karaś, Najderska, & Rogoza, 2017) of Grit-S also supported by the two-factor model. Datu et al (2016) carried out a study to validate the Grit-S among college and high school students in the Philippines.…”
Section: Introductionmentioning
confidence: 71%
“…Following the work of , the Grit-S has been formally translated into Japanese (Nishikawa et al, 2015), Turkish (Sarıçam et al, 2015), Filipino (Datu et al, 2016), German (Schmidt et al, 2017), Polish (Wyszyńska et al, 2017), Spanish (Arco-Tirado et al, 2018), and Chinese (Wang et al, 2017;Li et al, 2018;Zhong et al, 2018). Overall, cross-sectional data show that each version of the Grit-S has acceptable psychometric properties and that each translation resembles the English-speaking version (see Table 1).…”
Section: The Grit Scale and Its Short Versionmentioning
confidence: 99%